Islamic Economic Civilization During the Abbasid Period as the Foundation of Modern Islamic Economics - Sarina Junita; Khusnudin (al-Afkar, Journal For Islamic Studies, 2025)
The more advanced and the longer the gap between the lifetime of the Prophet Muhammad and the subsequent eras of governance, the more changes occurred in social, political, and economic structures. Although the principles taught remain guiding standards, the evolving challenges of time require adjustments in applying these values. This illustrates how the implementation of Islamic teachings must remain relevant to different contexts, both in governance and social life. The Abbasid dynasty, extending into the modern era, brought significant changes, especially in economics. During the Abbasid period, the economy reached its golden age. The policies and measures taken during the Abbasid era had a profound impact on today's economy. The author examines how the Abbasid administration improved various economic sectors, such as irrigation, infrastructure, agriculture, mining, trade, and funding for scientific research. The author sees the potential of modern economies by applying the Abbasid system, hoping for a prosperous economy Similar to that of the Abbasid era. This research was conducted using a qualitative literature review methodology, drawing from scholarly works and relevant magazines. The research findings reveal that there are similar values and policies that have been carried over into the present day, which were inspired by the Abbasid period.